P314 Identifying key stakeholders and their roles in the integration of POCTs for STIs into clinical services. (14th July 2019) - Pacho, Agata; De-Allie, Emma Heming; Furegato, Martina; Harding-Esch, Emma; Tariq Sadiq, S; Fuller, Sebastian
Abstract : Background: Despite potential to positively impact patient management, sequelae, and patient perceptions of services, few point-of-care tests (POCTs) to diagnose sexually transmitted infections (STIs) have been implemented into sexual health services (SHSs). Qualitative, in-depth research can be used to identify who the decision-makers are for adopting and implementing STI-POCTs in UK SHSs, and better understand these decision-makers' roles in these processes. Methods: We conducted a secondary analysis of data collected in two studies ( Precise and Facilitators to Adoption) . Based on their self-identified role in the POCT adoption process, sexual healthcare professionals (HCPs) were invited to in-depth interviews and workshops where participant observation notes were taken. Using these data, we defined key stakeholders and, using a thematic approach in NVIVO 11, we explored the process of POCT integration into their services. Results: 8 SHS workshops took place in 2017 and 37 interviews in 11 UK SHS took place between 2015 and 2018. Participants included clinicians, nurses, clinic managers, laboratory staff and clinical commissioners. Lead clinicians and managers self-identified themselves as key stakeholders for the decision to purchase, while nurses self-identified themselves as change champions for POCT implementation following adoption. Although many participants considered senior clinical staff most likely to introduce and drive change, participants stressed the importance of engagement of all clinical staff, particularly when tackling resistance to change. Conclusion: Our data suggest that supportive interpersonal relationships, such as between clinical leads and commissioners when considering adoption, and between all levels of clinical staff during implementation, must be considered to ensure the successful integration of POCTs in SHSs. Disclosure: No significant relationships.